Breaking Down The Black Box Of Industry Platform Processes : A Systematic Literature - Abed Alghani, Khaled; Kohtamäki, Marko (University of Aston, 2023)
Purpose: Despite the increasing prevalence of industry platforms, we still lack a comprehensive understanding of the processes that platform owners should undertake. Our knowledge of how these platforms are created, how they attract and integrate various actors, how they design governance mechanisms, how they manage internal and external issues, and how they evolve remains fragmented across different literatures. Moreover, our understanding of the antecedents and outcomes of these processes is limited. Design/Methodology/Approach: A systematic literature review of 442 articles from top-tier journals focused on industry platforms. Findings: This study makes three significant contributions: (1) identifying the key processes that platform owners pursue in the context of industry platforms, (2) identifying the antecedents and outcomes of these processes, and (3) presenting a comprehensive research agenda to guide future research on industry platforms. Originality/Value: Although previous literature reviews on this topic and other related ones have contributed valuable insights to the literature and we have leveraged them to enhance our understanding of industry platforms, none of these studies have comprehensively examined the processes involved in a platform owner's journey, including their antecedents and outcomes. Therefore, this study is the first to address this gap in the literature by comprehensively examining the black box of industry platform processes that platform owners undergo.
Keywords: industry platforms; two-sided markets; digital platforms; multi-sided platform; network effects; micro-processes; fi=Strateginen johtaminen|en=Strategic Management|